Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Sistem Persamaan Linear Dua Variabel Ditinjau dari Prestasi Belajar Siswa - Nurhalisah, Nurhalisah; Ruslan, Ruslan; Arwadi, Fajar (Issues in Mathematics Education (IMED), 2025)
This research aims to analyze students’ errors and the factor that cause students’ errors in solving problem of two-variabel linear equations system in terms of student achievement. This research is a qualitative research with a descriptive approach. The subjects in this study were class IX students of SMP Negeri 26 Makassar consisting of 9 people, namely three students with high learning achievement in mathematics, three students with moderate learning achievement, and three students with low learning achievement. Researchers took three people subject for each category with the consideration that tree people are enough to answer research purpose. The sampling technique used in this study is purposive sampling because the researcher took the subject based on the criteria set by the researcher. This determination carried out in accordance with the consideration that the sample taken canrepresent the population. Data collection techniques in this study were written tests and interviews. Data analysis techniques include data condensation, data presentation, and drawing conclusions. The results showed that: (1) the mistakes made by students with high mathematics achievement were wrong in understanding the questions, students were wrong in making mathematical models, and wrong in completing mathematical models; (2) students with mathematics learning achievements are making mistakes in understanding the questions, students are wrong in making mathematical models, and are wrong in completing mathematical models, and the final results are wrong; (3) students with learning achievement low mathematics make mistakes in understanding the questions, students make mistakes in making mathematical models, and wrong in completing mathematical models. The factors that cause student errors in solving SPLDV material questions include students being in a hurry so they are not careful in working on questions, difficulty finding words to be used as examples, misconceptions occur, wrong writing, difficulty understanding the meaning of the sentence proposed in the problem, lack of mastery of algebraic arithmetic operations, lack of mastery of SPLDV solving steps , lack of practice word problems, lack of mastery of the methods used in solving SPLDV questions, and as a result of errors in the previous step.